High-strength ß stabilized Ti-Nb-Fe-Cr alloys with large plasticity - Rabadia, C.; Liu, Y.; Cao, G.; Li, Y.; Zhang, C.; Sercombe, T.; Sun, Hongqi; Zhang, L. (Elsevier S.A., 2018)
A group of Ti-27Nb-7Fe-xCr (x = 0, 2, 4, 6, 8 wt%) alloys were designed on the basis of the DV-Xa cluster method, molybdenum equivalent and valence electron to atom ratio. The designed alloys were produced using the cold crucible levitation melting process for studying their microstructures and mechanical properties. The alloying of Cr renders a dual phase microstructure composed of a dominant ß and a small amount of orthorhombic a” formed in the Ti-27Nb-7Fe alloy to a single ß phase microstructure formed in the alloys containing Cr. In the present work, yield strength is influenced by the effects of solid solution strengthening and fine grain strengthening, whereas hardness is influenced by the phases present and the level of the ß stability. None of the investigated alloys fail until the load reaches 100 kN and all demonstrate impressive maximum compressive strength (~ 2 GPa) as well as plastic strain (> 26%). Young's modulus decreases from 116 GPa (for Ti-27Nb-7Fe) to 72 GPa (for Ti-27Nb-7Fe-8Cr) as the ß stability improves. Moreover, the analyses of slip band patterns around the hardness indentation, wear resistance indices (i.e. H/E and H3/E2) and elastic energies of the Ti-27Nb-7Fe-xCr alloys are carried out in the present work.